Decadal Variations in the Relationship between the Western Pacific Subtropical High and Summer Heat Waves in East China - Liu, Qi; Zhou, Tianjun; Mao, Huiting; Fu, Congbin (Journal of climate, 2019)
The western Pacific subtropical high (WPSH) is regarded as the key circulation system that dominates the summer heat waves over eastern China, but whether the WPSH–summer heat wave connection changes with time remains unknown. In this study, decadal variations in the WPSH–heat wave connection were examined for the period 1959–2016 using daily maximum temperature data from 654 observational stations across China and global reanalysis datasets. The results show that the correlation coefficient between the WPSH intensity (WPSHI) and the number of heat-wave days (NHD) was 0.65 (>99% confidence level) during positive phases of the Pacific decadal oscillation (PDO), whereas that during negative phases of the PDO was only 0.12 (<80% confidence level). The remarkable difference in correlations is due to the more westward extension of a stronger WPSH in El Niño decaying summers during the positive phases of PDO. The stronger Indian Ocean warming in El Niño decaying-year summers for PDO positive phases in comparison to PDO negative phases is associated with enhanced convection and heating, which further drive a stronger anticyclone over the northwestern Pacific, leading to a stronger and more westward-extending WPSH, which is favorable for more heat waves over eastern China.